Perubahan Kebijakan Iklim Inggris Terkait Target Net Zero Emission Global - Haniq, Raihan; Apriwan; Dermawan, Rifki (Hubungan Internasional Universitas Andalas, 2025)
This research was conducted to see changes in UK policy related to the Net Zero Emission target analyzed using the concept of foreign policy change by Jakob Gustavsson by looking at the factors that influence UK policy changes and the level of policy change. There are two factors, namely international factors and domestic factors seen from an economic and political perspective. Meanwhile, the level of policy change consists of four levels, namely Adjustment Changes, Program Changes, Problem/Goal Changes, and International Orientation Changes. This research uses descriptive qualitative methods. In this study, international factors in terms of the economy are caused by the decline in the global economy due to Covid-19, and in terms of politics is the conflict between Russia and Ukraine. As for domestic factors in terms of the economy is inflation in the UK, and domestic factors in terms of politics are the change of prime minister and political parties. Then, the level of policy change is at the level of Problem/Goal Changes and International Orientation Changes. Broadly speaking, the UK has not changed its target towards Net Zero Emission Global, but the existing policy changes can affect the UK's achievement of the target.